Effects of salinity on nitrification efficiency and bacterial community structure in a nitrifying osmotic membrane bioreactor. (October 2018) - Jeong, Dawoon; Cho, Kyungjin; Lee, Chang-Ha; Lee, Seockheon; Bae, Hyokwan
Graphical abstract: Highlights: Bacterial population dynamics were studied in an osmotic membrane bioreactor. Ammonia, alkalinity, and salinity caused changes in the bacterial community. Increased salinity led to NOB activity inhibition at 17.3 g-TDS/L. AOB were more tolerant than NOB to the high ammonia-loading rate and salinity. Nitrosomonas eutropha was dominant at high ammonia and salt concentrations. Abstract: The objective of this study was to evaluate the effects of salt accumulation on nitrifying bacterial communities in a nitrifying bioreactor combined with forward osmosis. The conversion of nitrite to nitrate was inhibited at a total dissolved solids (TDS) concentration of 17.3 g/L, whereas conversion of ammonia to nitrite was inhibited at a higher concentration (52.8 g-TDS/L). The gene copies of ammonia-oxidizing bacteria (AOB) were more abundant than those of nitrite-oxidizing bacteria (NOB) throughout the entire operating period of 225 days. Among NOB, the number of copies of Nitrobacter spp. were 100–1000 times higher than those of Nitrospira spp. A total of 140 operational taxonomic units were identified using 454 pyrosequencing. The relative abundances of autotrophic AOB and NOB accounted for 34.1–57.8% during 225 days. Dominance of Nitrosomonas eutropha was stable as a salt-tolerant AOB, but the representative NOB, Nitrobacter winogradskyi, showed salt-sensitive variations in their relative abundance. Nonmetric multidimensional scaling and hierarchical clustering analysis clearly illustrated the shift in bacterial community due to external conditions, i.e., ammonia loading rate, alkalinity availability, and salinity. Heterotrophic bacteria contributed to changes in overall bacterial community structure in the nitrifying osmotic membrane bioreactor despite the absence of carbon sources in the influent.